Hedonic Test of Pegagan Chocolate Products at PT XYZ - Iryani, Dian; Hidayah, Nurul (Universitas Ahmad Dahlan, 2021)
Handling of raw materials for cocoa beans is an important process to maintain the quality of the processed chocolate. There are several stages carried out in the post-harvest cocoa process including fruit picking, fruit breaking, cocoa bean fermentation, drying cocoa beans and storage. The purpose of this study was to determine whether or not a sensory assessment of the preference for pegagan chocolate was made, and to analyze the panellists’ level of acceptance of pegagan chocolate. Pegagan leaf chocolate is produced with the aim of providing good nutrition, brain multivitamins and memory enhancers. Sensory assessment of the hedonic test using 20 untrained panellists from the parameters measured were color, taste, texture, aroma and shape. The panellists’ acceptance of chocolate with the addition of pegagan leaves was that the majority liked the chocolate on all parameters.